Reproduction Period Of Javanese Women - Kusumawati, Eka Dewi; Kawulur, Elda Irma Jeanne Joice; Rohmatullayaly, Eneng Nunuz (Journal of Nursing Care, 2023)
A woman's reproductive life goes through several phases including menstruation, childbirth and menopause. The first menstrual event experienced by a woman is called menarche, while the end of the menstrual period is called menopause. The age intervals for menarche and menopause describe the reproductive period or fertile age for a woman to become pregnant and give birth. The postreproductive period characterized by menopause is related to a woman's life expectancy and is important for assessing the quality of life. This research aims to determine the reproductive period of Javanese women in Oransbari, South Manokwari Regency. Cross-sectional research was conducted on women with an average age of 51.73 years with an interval of 40.18-69.59 years. The inclusion criteria were women who had experienced menopause. The age of menarche and menopause were analyzed using the Generalized Linear Model (GLM) in the R program. We found that the age at menarche (12.3 years) and age at menopause (43.1 years) of Javanese women in Oransbari were relatively young. This condition results in a shorter reproductive period (30.8 years) compared to several populations in Indonesia such as Sunda, Baduy, Tengger, Lampung, and Semendo. The reproductive period, which tends to be short, might be an adaptive response to environmental challenges that were less favourable as a pioneer transmigration society, such as high physical activity and low socio-economic conditions. The biocultural conditions experienced in the early life of Oransbari form a reproductive period that starts and ends early as an adaptive response to maximize reproductive success. Thus, women's reproductive health especially communities in isolated and remote areas, needs to be studied and become one of the government's focuses in considering intervention policies related to the health and welfare of the elderly and demographics